The development of real-time polymerase chain reaction for identification of beef meatball - Abdul Rohman; Salmah Orbayinah; Adam Hermawan; Sismindari Sudjadi; Anjar Windarsih; Sri Handayani (Applied Food Research, 2022)
Real-time polymerase chain reaction (PCR), also known as quantitative PCR (qPCR), is a method of choice for the confirmation of halal meats such as beef from non-halal meats such as pork through analysis of their deoxyribonucleic acid (DNA). The objective of this study was to apply qPCR in combination with species-specific primer (SSP) targeting in D-loop mitochondria genes for the identification of DNA extracted from beef and beef meatballs. DNA in raw meats and meatballs was isolated using Genomic DNA Mini Kit and the obtained DNAs were subjected to SSP specificity, amplification efficiency (E), determination of limit of detection (LoD), and repeatability test. The results showed that SSP designed was specific to beef DNA with LoD value of 100 ng beef DNA. The coefficient of determination (R2) for the relationship between log DNA concentration and quantification cycle (Cq) along with efficiency values were 0.884 and 97.1% respectively. The developed method is precise enough as indicated by the low value of relative standard deviation (RSD) value of 0.77%. The qPCR method using SSP is also successfully applied for analysis of beef meatballs commercially available. It can be concluded that qPCR using SSP targeting on D-loop mitochondria could be proposed as a standard method for the confirmation beef meatballs.